Respon Morfo-Fisiologis Cabai Rawit (Capsicum frutescens L.) terhadap Genangan Air dan Pemberian Bakteri Rhizosfer Leguminosae - Pahlevi, Muhammad Rizza; Kurniahu, Hesti; Andriani, Riska (Universitas Nahdlatul Ulama Blitar, 2025)
Cayenne pepper is known to be susceptible to various types of flooding by showing various negative responses. This study seeks to ascertain the influence of PGPR on the adverse effects of floods on cayenne pepper as a means to mitigate farmer losses. The study used a completely randomized design on cayenne pepper which was given treatments in the form of control without PGPR (K(-)), control with PGPR (K(+)), flooding treatment for 2 days with PGPR 7 days later (P(+)) and without PGPR (P(-)) each with 10 reps. The two-way ANOVA test reflected that flooding had a significant effect on the response of plant height increase, petiole curvature angle, and wilting. In contrast, PGPR application had a significant effect on plant height increase and number of branches. The interaction of flooding and PGPR application significantly affects the increase in plant height but not the number of leaves, the number of branches, the angle of curvature of the petiole, and wilting. It was concluded that the application of PGPR can reduce the adverse effects of flooding on cayenne pepper farming.